The Effect of Problem-Based Learning on Critical Thinking Skills in Islamic Religious Education: A Quasi-Experimental Study in an Indonesian Vocational High School - Agus Fawait; Kuratul Ayuni; Diah Kartika Sari (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2026)
This study examined the effect of Problem-Based Learning (PBL) on students' critical thinking skills in Islamic Religious Education (IRE) at a vocational high school in Indonesia. A nonequivalent control group quasi-experimental design was employed with 66 Grade XI students at State Vocational High School 02 Bondowoso, selected through purposive sampling and divided equally into an experimental class (PBL) and a control class (conventional instruction). Data were collected using a 17-item PBL implementation scale, a 16-item critical thinking scale (both on a four-point Likert scale), and pre-test/post-test assessments. Instruments were validated using Pearson Product Moment correlation and confirmed reliable via Cronbach's Alpha (α > 0.60). Data were analyzed using an independent sample t-test and simple linear regression with IBM SPSS version 25. The t-test revealed a statistically significant difference between groups, t(64) = 2.079, p = 0.042, with the experimental group achieving a higher mean score (M = 56.18) than the control group (M = 54.15). Simple linear regression confirmed a significant predictive model, F(1, 64) = 9.481, p = 0.003, R² = 0.129, with a standardized coefficient β = −0.359. These results indicate that PBL significantly affects students' critical thinking skills in IRE; however, optimal outcomes require improvements in teacher facilitation quality and student readiness for inquiry-based learning.